Biofilm Dispersal in Bacillus velezensis FZB42 Is Regulated by the Second Messenger c-di-GMP - Meiyu Zhang; Shanyou Wu; Peng Chen; Lin Shao; Zizhu Shen; Yinjuan Zhao (Microorganisms)
Cyclic diguanosine monophosphate (c-di-GMP) is a second messenger that plays a crucial role in regulating biofilm development, yet the role in Gram-positive bacteria remains elusive. Here, we demonstrated that dispersed cells from biofilms of Bacillus velezensis FZB42 exhibit a unique phenotype and gene expression compared to planktonic cells. Transcriptomic analysis revealed 1327 downregulated and 1298 upregulated genes, among which the c-di-GMP phosphodiesterase coding yuxH gene was remarkably upregulated. Deletion of the yuxH gene led to elevated c-di-GMP levels accompanied by reduced amounts of “actively dispersed cells” from the pellicle and the capacity of motility. Deletion of spoIIIJ, spo0J, and kinA resulted in increased c-di-GMP levels and reduced biofilm dispersal ability. Also, the level of c-di-GMP was increased when adding the cues of inhibition biofilm dispersal such as glucose and calcium ions. Collectively, these present findings suggest the c-di-GMP level is negatively correlated with biofilm dispersal in Bacillus velezensis FZB42, which sheds new light on biofilm regulation in Bacillus velezensis FZB42.